Wielopłaszczyznowy charakter lekcji języka obcego - Siek-Piskozub, Teresa; Wach, Aleksandra (Studia Rossica Posnaniensia, 2013)
A foreign language lesson is an interesting and complex event, with a specific structure, social roles ascribed to the participants, and a set of relevant objectives which it aims to fulfill as part of a certain teaching methodology. Following the various perspectives on a lesson which were identified by Prabhu1, the article aims to emphasize the multidimensional nature of a foreign language lesson. Therefore, a lesson is scrutinized as a basic unit of a syllabus, as a way of operationalizing a teaching method, as a social event, as a scene of social interaction, and as an experience fostering the development of teachers’ competence.